3D, 4D and 5D of Buiding Information Modeling for Real Estate Projects: Optimizing Real Estate Projects through Building Information Modeling (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Now a day in India, Technology is changing rapidly in construction industry as well as Government is also forming new laws for real estate. This paper tells about, How Building Information Modeling (BIM) is useful for implementing the RERA (real estate and regulation act). Under real estate and regulation act, builder or developers have to submit lot of information to government. This information we builder or developer have to preserve for future use but by use of BIM it is very easy to save data and to make virtual model of whole project which is to be executed. Project duration and cost are two major factors in execution of project. With the use of building information modeling, both of these factors can be optimized.